2013
DOI: 10.1111/tpj.12230
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis plants lacking PsbQ and PsbR subunits of the oxygen‐evolving complex show altered PSII super‐complex organization and short‐term adaptive mechanisms

Abstract: These authors contributed equally to this work. SUMMARYThe oxygen-evolving complex of eukaryotic photosystem II (PSII) consists of four extrinsic subunits, PsbO (33 kDa), PsbP (23 kDa), PsbQ (17 kDa) and PsbR (10 kDa), encoded by seven nuclear genes, PsbO1 (At5g66570), PsbO2 (At3g50820), PsbP1 (At1g06680), PsbP2 (At2g30790), PsbQ1 (At4g21280), PsbQ2 (At4g05180) and PsbR (At1g79040). Using Arabidopsis insertion mutant lines, we show that PsbP1, but not PsbP2, is essential for photoautotrophic growth, whereas pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 66 publications
(98 reference statements)
10
84
0
Order By: Relevance
“…ami-RNA-psbr-2. Likewise, the data revealed that subunits PSBP and PSBQ were both diminished in amounts in conjunction with PSBR, in agreement with data obtained for Arabidopsis PSBR-deficient plants (Suorsa et al, 2006;Liu et al, 2009;Allahverdiyeva et al, 2013). On the other hand, other PSII core subunits or the minor core PSII light-harvesting proteins, LHCB4 and LHCB5, were not significantly altered in their protein ratios in both ami-RNA-psbr strains.…”
Section: Diminishment Of Psbr Expression Destabilizes the Binding Of supporting
confidence: 79%
See 4 more Smart Citations
“…ami-RNA-psbr-2. Likewise, the data revealed that subunits PSBP and PSBQ were both diminished in amounts in conjunction with PSBR, in agreement with data obtained for Arabidopsis PSBR-deficient plants (Suorsa et al, 2006;Liu et al, 2009;Allahverdiyeva et al, 2013). On the other hand, other PSII core subunits or the minor core PSII light-harvesting proteins, LHCB4 and LHCB5, were not significantly altered in their protein ratios in both ami-RNA-psbr strains.…”
Section: Diminishment Of Psbr Expression Destabilizes the Binding Of supporting
confidence: 79%
“…On the other hand, the major light-harvesting proteins LHCBM1 and LHCBM3 were slightly diminished in the PSBR knockdown strains, suggesting that PSII-LHCII complex formation is impaired by PSBR depletion. In line with this, it was reported that in PSBR-deficient Arabidopsis plants, the formation of PSII-LHCII supercomplexes was marginally affected (Allahverdiyeva et al, 2013). Interestingly, deletion of LHCBM1 resulted in a significant decrease of NPQ (Elrad et al, 2002) in C. reinhardtii.…”
Section: Psbr Is Involved In Forming a Recognition Site For The Bindisupporting
confidence: 59%
See 3 more Smart Citations